Accounting Quality and Long Term Shareholder Value Creation (gjstudies, 2017)
This research introduces a novel methodological framework for examining the relationship between accounting quality and long-term shareholder value creation, departing from traditional econometric approaches by integrating principles from complexsystems theory and computational linguistics. We conceptualize financial reportingnot as a static informational input but as a dynamic signaling system within corporateecosystems, where accounting quality functions as a coherence mechanism betweenmanagerial actions, market perceptions, and fundamental value. Our methodologyemploys a multi-agent simulation model that represents heterogeneous market participants with varying information processing capabilities, coupled with a text analysiscomponent that evaluates narrative disclosures using entropy-based measures of informational content. We formulate three unconventional research questions: (1) How doesthe fractal dimensionality of accounting information flows influence value persistenceacross different market regimes? (2) What is the role of disclosure narrative complexityin moderating the relationship between accounting precision and long-term value creation? (3) How do emergent properties in investor interpretation networks affect thetranslation of accounting quality into shareholder returns? Our simulation results, derived from 50,000 firm-period observations generated through our agent-based model,reveal several counterintuitive findings. First, we identify a non-monotonic relationshipbetween accounting precision and long-term value creation, with optimal value accrualoccurring at intermediate levels of precision rather than maximal precision, challenging conventional wisdom. Second, we demonstrate that moderate narrative complexityin disclosures enhances the value relevance of accounting information, while both excessive simplicity and complexity degrade it. Third, we find that network effects ininvestor interpretation create path dependencies where early consensus on accountingquality can become self-reinforcing, decoupling from underlying fundamentals. Thesefindings contribute original insights to accounting, finance, and information economicsby reconceptualizing accounting quality as a systemic property rather than an attributeof individual reports, with implications for standard-setting, corporate disclosure practices, and investment strategies focused on long-term value creation.